The Effect of Drying and Roasting Times on Sensory and Physicochemical Characteristics of Ground Roasted Coconut - Sri Hartuti; Juanda Juanda; Mustaqimah Mustaqimah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Ground roasted coconut is used as a cooking spice, especially in Aceh, with distinctive aroma and fragrant taste. This study aimed to examine the effect of drying time and roasting time on the sensory and physicochemical characteristics of roasted coconut. This research was designed with two treatment factors in triplicate. First factor was the drying time (1, 3, and 5 h), and second factor was roasting time (5 and 10 min). The results showed that drying time has a significant effect on the aroma, color, taste, and air content. The longer the drying time, the higher the sensory characteristics: aroma, color, and taste of ground roasted coconut, but the percentage of water content of the roasted coconut produced is lower. The roasting time also affected the taste and aroma of ground roasted coconut. The longer the roasting process, the higher the sensory characteristics of the taste and aroma of ground roasted coconut. The interaction of drying time and roasting time only has an effect on the sensory taste of ground roasted coconut. Drying time and roasting time did not significantly affectted on fat content and free fatty acid content, both of these parameters are more influenced by other factors, such as drying temperature, harvest age and coconut quality.